2015
DOI: 10.5851/kosfa.2015.35.3.370
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effect of Carrot and Lemon Fiber as a Fat Replacer on Physico-chemical, Textural, and Organoleptic Quality of Low-fat Beef Hamburger

Abstract: This study was designed to determine the usability of lemon fiber (LF-2%, 4%, 6%) and carrot fiber (CF-2%, 4%, 6%) to produce low-fat beef hamburgers. To that end, a certain amount of fat was replaced with each fiber. The proximate composition, pH value, cholesterol content, cooking characteristics, color, texture profile, and sensory properties of low-fat beef hamburgers were investigated. LF increased moisture content and cooking yield due to its better water binding properties, while CF caused higher fat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…The pH values of raw beef burgers were significantly reduced (P ≤0.05) with the replacement of fat by orange albedo flour, ranging from 6.16 (FC) to 5.42 (F4-100), which could be due to the pH of the orange albedo flour (pH = 5.00). Similar results were reported by other works (Aleson-Carbonell et al, 2005;López-Vargas et al, 2014;Sariçoban et al, 2008;Soncu et al, 2015).…”
Section: Proximate Composition and Ph Of The Orange Albedo Flour And supporting
confidence: 92%
See 3 more Smart Citations
“…The pH values of raw beef burgers were significantly reduced (P ≤0.05) with the replacement of fat by orange albedo flour, ranging from 6.16 (FC) to 5.42 (F4-100), which could be due to the pH of the orange albedo flour (pH = 5.00). Similar results were reported by other works (Aleson-Carbonell et al, 2005;López-Vargas et al, 2014;Sariçoban et al, 2008;Soncu et al, 2015).…”
Section: Proximate Composition and Ph Of The Orange Albedo Flour And supporting
confidence: 92%
“…Similarly to this work, López-Vargas et al (2014) also did not report any difference in coordinate b* in pork burgers incorporated with up to 5 % of passion fruit albedo. Other authors showed the yellowness increased in beef burgers made with lemon albedo (Aleson-Carbonell et al, 2005), and lemon fiber (Soncu et al, 2015). The whiteness (W) value, which correlates the coordinates L*, a*, and b*, did not differ between treatments.…”
Section: Cooking Parameters Whc and Color Of Beef Burgersmentioning
confidence: 90%
See 2 more Smart Citations
“…Functional properties of processed meat products made with different fiber sources have been studied. Use of peach fiber in low fat frankfurters (Grigelmo-Miguel, Motilva-Casado, & Martin-Belloso, 1997), β-glucan rich fiber in breakfast sausage (Aleson-Carbonell, Fernandez-Lopez, Perez-Alvarez, & Kuri, 2005), rice bran fiber in reduced fat frankfurters (Choi et al, 2010), orange fiber in fermented sausage called Sucuk (Yalinkilic, Kaban, & Kaya, 2012), yellow passion fruit fiber in pork burgers (Lopez-Vargas, Fernandez-Lopez, Perez-Alvarez, & Viuda-Martos, 2014) and carrot and lemon fiber in low-fat beef hamburgers (Soncu et al, 2015) have been helpful for improving functional properties of meat products. According to Gorinstein et al (2001), citrus peel (albedo and flavedo) is rich in soluble fiber and can be used in meat products as a functional ingredient.…”
Section: Introductionmentioning
confidence: 99%